2022
DOI: 10.1039/d2cp02129c
|View full text |Cite
|
Sign up to set email alerts
|

No more compromise: a facile route towards functionalized surfaces with stable monolayers

Abstract: The results reported in this study clearly show that it is possible to easily control the formation of a functional monolayer by spontaneous reduction of an aryldiazonium salt on gold...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…This structural modification offers two significant advantages. First, as demonstrated in previous studies, 19,20 the 12-carbon alkyl chain restricts electron tunneling through the organic layer, resulting in growth limitation to a monolayer. Second, the alkyl chain acts as a barrier, nullifying the electronic effect of the functional group.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…This structural modification offers two significant advantages. First, as demonstrated in previous studies, 19,20 the 12-carbon alkyl chain restricts electron tunneling through the organic layer, resulting in growth limitation to a monolayer. Second, the alkyl chain acts as a barrier, nullifying the electronic effect of the functional group.…”
Section: Introductionmentioning
confidence: 81%
“…The grafting potential was then applied to generate aryl radicals from in situ generated diazoniums, following the procedure described in previous literature. 19,20 The counter electrode used was a platinum (Pt) rod, and the reference electrode was Ag/AgNO 3 (0.01 M in 0.1 M nBu 4 NPF 6 in acetonitrile). After deposition of the organic layers, the GC electrodes were sonicated for 2 minutes and washed with DCM.…”
Section: Electrochemical Graftingmentioning
confidence: 99%
See 1 more Smart Citation
“…If the last two aforementioned articles do not extend the studies toward obtaining similar molar ratios between grafted species and those in solution, they nevertheless highlight the beneficial impact of increasing the distance between the functional group and the diazonium function through the introduction of methylene bridges. A recently described method has taken a further step by introducing a 12-carbon alkyl chain between the aromatic ring and the functional group, thereby canceling out its electronic effect. , Such homogenization of the considered diazonium structures has (i) standardized the reduction potentials regardless of the end group (Δ E = 50 mV), (ii) enabled equalization of the radical’s reactivity, and (iii) made the steric hindrance of the molecules involved uniform, thereby allowing precise stoichiometric control of the immobilized species . Consistent electrochemical, spectroscopic, and XPS results showed that mixed layers with controlled composition closely resembling that of the original diazonium mixture were obtained via this approach.…”
Section: Simultaneous Reduction Of Two Diazonium Saltsmentioning
confidence: 99%
“…16−19 However, a certain fragility in the molecular structures formed has been demonstrated, particularly under exposure to air, 20 heat, 21 or electrochemical stresses. 22 These limitations, problematic for applications requiring exposure to ambient conditions, 23 likely account for the increasing interest in the more robust thin layers achieved through the reduction of aryldiazonium cations. This reduction, whether spontaneous or electrogenerated, gives rise to the formation of highly reactive radicals.…”
Section: ■ Introductionmentioning
confidence: 99%